2022
DOI: 10.1182/bloodadvances.2021006018
|View full text |Cite
|
Sign up to set email alerts
|

A genetically distinct pediatric subtype of primary CNS large B-cell lymphoma is associated with favorable clinical outcome

Abstract: Primary central nervous system large B-cell lymphoma (PCNS-LBCL) occurs typically in older adults and only rarely in the pediatric population. The genomic landscape of PCNS-LBCL in children and young adults (YA) is not well-characterized. In this multi-institutional study, targeted next-generation DNA sequencing and chromosomal copy number analysis was performed on a cohort of 12 pediatric and YA (age<40 years) PCNS-LBCL patients without known immunodeficiency and correlated with clinicopathologic data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Two of the eight cases submitted (LYWS-532, Uner A, et al Duzen Laboratories, Ankara, Turkey; and LYWS-363, Wilson CS, et al University of New Mexico Health Sciences Center, Albuquerque, USA) were pediatric cases, both with morphology that was felt to be more in keeping with DLBCL, nos. The third pediatric case (LYWS-595, Shafernak K et al Phoenix Children’s Hospital; Phoenix, AZ, USA) was felt to represent a primary DLBCL of the central nervous system (CNS), which are extremely uncommon, and virtually only reported as case reports [ 52 55 ].…”
Section: High-grade B-cell Lymphoma Nosmentioning
confidence: 99%
“…Two of the eight cases submitted (LYWS-532, Uner A, et al Duzen Laboratories, Ankara, Turkey; and LYWS-363, Wilson CS, et al University of New Mexico Health Sciences Center, Albuquerque, USA) were pediatric cases, both with morphology that was felt to be more in keeping with DLBCL, nos. The third pediatric case (LYWS-595, Shafernak K et al Phoenix Children’s Hospital; Phoenix, AZ, USA) was felt to represent a primary DLBCL of the central nervous system (CNS), which are extremely uncommon, and virtually only reported as case reports [ 52 55 ].…”
Section: High-grade B-cell Lymphoma Nosmentioning
confidence: 99%
“…Capture-based next-generation sequencing (NGS) was performed at the UCSF Clinical Cancer Genomics Laboratory with UCSF500, a targeted sequencing panel consisting of all coding regions of 529 cancer-related genes and selected introns from 47 genes. Analysis of single nucleotide variants, insertion/deletions, structural variants including gene fusions, genome-wide copy number, and zygosity analysis, with a total sequencing footprint of 2.8 Mb was performed and bioinformatic analysis was performed using custom pipelines as previously described ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, through integration of molecular and clinicopathologic features, we have demonstrated that PTLD involving the CNS is a heterogeneous disease category comprising at least 3 distinct biologic types. The sporadic PCNS-LBCL–like type demonstrated a molecular profile with MYD88 and CD79B mutations similar to sporadic EBV − adult-type MYD88 -mutant primary CNS-LBCL, 22 which suggests that the pathogenesis is similar to that of conventional EBV − PCNS-LBCL in immunocompetent adults. The systemic Ras-driven type was defined by systemic extra-CNS involvement and activating RAS family oncogene mutations, similar to those reported in systemic PTLD.…”
mentioning
confidence: 86%
“…However, the genetic landscape of PTLD involving the CNS is not well established, with the most comprehensive study including cases of PTLD-CNS demonstrating that EBV + and HIV − cases had a low burden of somatic mutations with a lack of alterations in MYD88 , CD79B , PIM1 , and CDKN2A/B known to be frequent in adult-type MYD88 -mutant primary CNS large B-cell lymphoma (PCNS-LBCL), as well as mutations in TP53 , NKFBIE , and GNA13 that we recently described as frequent in pediatric-type MYD88 -wild-type PCNS-LBCL. 19 , 20 , 21 , 22 , 23 …”
mentioning
confidence: 99%